42.8k views
2 votes
(a-√a/√a-1) - (√a+1/a+√a) : √a+1/a. solve a

1 Answer

7 votes

Answer:

Explanation:


\displaystyle \ \Large \boldsymbol{} (a-√(a) )/(√(a)-1 ) -(√(a)+1 )/(a+√(a) ) :(√(a)+1 )/(a) = \\\\\\(√(a)(√(a) -1 ) )/((√(a)-1) ) -(√(a)+1 )/(√(a)(√(a)+1 ))\cdot (√(a)\cdot √(a) )/(√(a)+1 ) = \\\\\\√(a) -(√(a) )/(1+√(a) ) =(a+√(a)-√(a) )/(1+√(a) ) = \\\\\\(a)/(√(a)+1 ) \cdot (√(a)-1 )/(√(a)-1) } =\boxed{(a√(a) -a)/(a-1) }

User Anquegi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.